Sistem Informasi Penjualan Berbasis Web Pada UMKM R-DUA Lencana Kudus - Robby Novianto; Maryam (Jurnal Teknoif Teknik Informatika Institut Teknologi Padang, 2022)
R-Dua Lencana is one of the SMEs in the Kudus Regency area. These MSMEs sell badges which are official identifications that are painted with symbols and in the form of medals which are usually used as a sign of being a member of an agency or organization. Currently, R-Dua Lencana sells its products only in stores and has not used the internet much as a means of promotion so it will experience a decline in sales. Therefore, a website-based sales information system was designed to expand sales, becoming a means of product promotion, providing time and travel cost efficiency, and getting new customers. The method used in this development uses SDLC (System Development Life Cycle) using a waterfall model starting from requirements analysis, system design, implementation or code writing, testing, and maintenance. This website utilizes Single Page Application (SPA) technology which is in the browser so that it does not require reloading when the website is used to switch pages. In this study, it has been tested using the BlackBox method with the results declared valid and the results of the SUS test with the results declared Acceptable so that it is feasible to use. Researchers hope that the information system designed can help the sale of MSME R-Dua Lencana Kudus.